(untitled) (Applied Biological Research, 2012)
The present paper gives flower morphology, anthesis, pollen production, foraging nature of flower visitors, pollination mechanisms, in vitro and in vivo pollen germination and stigma receptivity of ten medicinal plants viz., Aegle marmelos (L.) Correa (Rutaceae), Anthocephalus chinensis (Lamk.) A. Rich. (Rubiaceae), Averrhoa carambola Linn. (Oxalidaceae), Cassia fistula Linn. (Caesalpiniaceae), Catharanthus roseus (Linn.) G. Don. (Apocynaceae), Dillenia indica Linn. (Dilleniaceae), Madhuca indica Gmelin. (Sapotaceae), Pterospermum acerifolium Willd. (Sterculiaceae), Terminalia arjuna (Roxb. ex DC.) Wt. & Arn. (Combretaceae) and Vitex negundo Linn. (Verbenaceae). Species-wise variation on flower morphology, flower and pollen anthesis were observed. Pollen production flower-1ranged from 4000 to 613150 and log value for pollen production flower-1varied from 3.60 (in Vitex negundo) to 5.79 (in Aegle marmelos). Apertural types and exine ornamentation pattern of pollen grains were noticed to be specie-specific. During day time different members of Thysanoptera, Hymenoptera, Lepidoptera, Diptera and Coleoptera visited the flowers and enhanced pollination success rate in terms of fruit/seed set which was ascertained by netting and bagging process. In vitro pollen germination study indicated that the requirements of sucrose and minerals like boron, calcium, magnesium and potassium for optimum germination varied from species to species. Stigmas were more receptive during first day after anthesis in A. marmelos, A. chinensis, M. indica, T. arjuna and V. negundo. However, A. carambola, C. roseus and D. indica showed more receptive stigmas during 2nd day after anthesis whereas stigma were more receptive during 3rd day after anthesis in case of C. fistula and P. acerifolium.